1995
DOI: 10.1074/jbc.270.32.18734
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Contractility without an Increase in Basal Myosin Light Chain Phosphorylation in Wild Type Cells and Cells Expressing the Catalytic Domain of Myosin Light Chain Kinase

Abstract: We investigated the role of myosin light chain (MLC20) phosphorylation (MLC-P) in non-muscle contractility by comparing MLC-P and the contractile properties of wild type 3T3 fibroblasts and 3T3 fibroblasts expressing the catalytic domain of myosin light chain kinase (tMK). MLC-P is 0.96 MOL of PO4/mol of MOL20 in cell expressing tMK compared to 0.20 mol of PO4/mol of MLC20 in control cells. Expressing tMK also results in a 2-fold increase in cortical stiffness compared to control cells. Contractile properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…In vitro phosphorylation of MRLC at Thr18 and Ser19 stimulates the actin-activated ATPase of myosin II and filament assembly [15]. However, while manipulating the phosphorylation state of MRLC by overexpression of Thr18/Ser19 mutants has some effects on cell migration [16,17,18], other studies with pharmacological agents suggest that phosphorylation of MRLC is not necessary for migration [19]. The analysis is complicated by the involvement of multiple Ca2+ dependent and Ca2+ independent pathways in regulating MRLC phosphorylation at Thr18/Ser19; the former is mediated by the myosin light chain kinase (MLCK) downstream of Ca2+-calmodulin, while the latter may involve the Rhodependent kinase (ROCK), which may act directly on MRLC or through the myosin light chain phosphatase [20].…”
Section: Introductionmentioning
confidence: 97%
“…In vitro phosphorylation of MRLC at Thr18 and Ser19 stimulates the actin-activated ATPase of myosin II and filament assembly [15]. However, while manipulating the phosphorylation state of MRLC by overexpression of Thr18/Ser19 mutants has some effects on cell migration [16,17,18], other studies with pharmacological agents suggest that phosphorylation of MRLC is not necessary for migration [19]. The analysis is complicated by the involvement of multiple Ca2+ dependent and Ca2+ independent pathways in regulating MRLC phosphorylation at Thr18/Ser19; the former is mediated by the myosin light chain kinase (MLCK) downstream of Ca2+-calmodulin, while the latter may involve the Rhodependent kinase (ROCK), which may act directly on MRLC or through the myosin light chain phosphatase [20].…”
Section: Introductionmentioning
confidence: 97%
“…Obara et al also reported that stress fiber formation is important in fibroblasts to generate contraction force. 53) Kolodney and Wysolmerski further reported that phosphorylation of MLC plays a critical role in the force generation of fibroblasts induced by antagonists such as thrombin since the time course of the increase of MLC phosphorylation in response to thrombin closely paralleled the increase in isometric force. 5) In contrast, Obara et al demonstrated that increase of MLC phosphorylation is independent of the contraction force generation of fibroblasts induced by serum.…”
Section: Effects Of Various Kinase Inhibitors On Contraction Forcementioning
confidence: 99%
“…5) In contrast, Obara et al demonstrated that increase of MLC phosphorylation is independent of the contraction force generation of fibroblasts induced by serum. 53) Nobe et al investigated the mechanism of contraction force generation focusing on stress fiber formation, MLC phosphorylations, and force generation using a force measuring system similar to ours. 54) They reported that the Rho kinase inhibitor Y27632 inhibits force generation in fibroblasts and prevents stress fiber formation induced by serum, but does not affect MLC phosphorylation.…”
Section: Effects Of Various Kinase Inhibitors On Contraction Forcementioning
confidence: 99%
“…In addition to Rho kinase, the spatial and temporal pattern of MLC phosphorylation in fibroblasts is controlled by . Other mechanisms of force generation independent of MLC phosphorylation also have been described (18,19), even in smooth muscle cells (20,21) where MLC phosphorylation generally is thought to be the key regulator of contractile activity (22).The current studies were carried out to learn more about the molecular motors responsible for LPA-and PDGF-stimulated fibroblast-collagen matrix contraction. We found that neither PDGF-nor LPA-dependent contractile mechanisms require MLC kinase or increased phosphorylation of MLC (measured as diphosphorylation).…”
mentioning
confidence: 99%
“…In addition to Rho kinase, the spatial and temporal pattern of MLC phosphorylation in fibroblasts is controlled by . Other mechanisms of force generation independent of MLC phosphorylation also have been described (18,19), even in smooth muscle cells (20,21) where MLC phosphorylation generally is thought to be the key regulator of contractile activity (22).…”
mentioning
confidence: 99%